2021
DOI: 10.1097/htr.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Vestibular and Oculomotor Impairments Among Amateur Athletes 1 Year Following Sport-Related Concussion: A Prospective Follow-Up

Abstract: Objectives:To investigate (i) the presence of vestibular and oculomotor impairments and (ii) the self-perceived effects of concussion-associated dizziness on health-related quality of life among amateur athletes 6 months and 1 year following sport-related concussion compared with nonconcussed, control athletes. Design: Prospective, matchedcohort study. Setting: Clinical assessment laboratory. Participants: Amateur athletes who were diagnosed with sport-related concussion within 1 week of injury, and sex-, age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Other studies have tracked recovery of VOM function (84) to the authors knowledge, this is the first study to track recovery of VOM function using the VOMS tool at regular intervals within the initial 14 days post-SRC and following the graded RTP process. Other studies using VOMS have identified VOM dysfunction delays return to learn (85), ability to start graded return to exercise (86) or being medically cleared to RTP (10,87).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have tracked recovery of VOM function (84) to the authors knowledge, this is the first study to track recovery of VOM function using the VOMS tool at regular intervals within the initial 14 days post-SRC and following the graded RTP process. Other studies using VOMS have identified VOM dysfunction delays return to learn (85), ability to start graded return to exercise (86) or being medically cleared to RTP (10,87).…”
Section: Discussionmentioning
confidence: 99%
“…Although initially developed as a screening tool for the purpose of distinguishing between concussed and healthy adolescents,1–7 there has been growing interest from clinical and research teams to use this tool outside the scope of screening and with different populations8 (eg, addition of VOMS to Military Acute Concussion Evaluation 2 [MACE2]9). Such examples include use in subacute and persistent time frames,8,10–15 use with adults,8,15,16 and also for tracking recovery 8,16–18. Given changes that may occur throughout recovery (eg, expected improvements in some or all symptoms between 2 and 4 weeks),19 and known differences in the vestibular and oculomotor systems that occur with aging,20,21 findings from research conducted in younger and athletic populations may not be generalizable to adults following mTBI, especially those with symptoms that persist beyond expected recovery timelines.…”
mentioning
confidence: 99%
“…Such examples include use in subacute and persistent time frames, 8,[10][11][12][13][14][15] use with adults, 8,15,16 and also for tracking recovery. 8,[16][17][18] Given changes that may occur throughout recovery (eg, expected improvements in some or all symptoms between 2 and 4 weeks), 19 and known differences in the vestibular and oculomotor systems that occur with aging, 20,21 findings from research conducted in younger and athletic populations may not be generalizable to adults following mTBI, especially those with symptoms that persist beyond expected recovery timelines. Thus, further evidence is needed to support VOMS use outside its original scope including clinical use for nonathlete adults with concussion symptoms that persist beyond 3 weeks.…”
mentioning
confidence: 99%